Rekonstruksi Desain Kegiatan Laboratorium Kurikulum KTSP dan K-13 Pada Materi Ekosistem Untuk Mengembangkan HOTS Siswa - Muchsin, Adnan; Supriatno, Bambang; Anggraeni, Sri (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aims to analyze 4 (four) aspects in the Design of Laboratory Activities (DKL/Worksheet) on concept of ecosystem components and echological intearction in different curricula (KTSP 2006 and K-13), which could become a reference in reconstructing new Worksheet. The four aspects tested were relevance to the curriculum, competence, knowledge construction and practical aspect. The instrument developed in this study was a descriptive table refering to the Vee Diagram. This reserach used a qualitative descriptive method and all sampels of worksheets were collected using purposive sampling from various sources. The data were analyzed based on the percentage of total scores gained in the rubric and were categorized based on the tabel of validity criteria.The steps of the research were conducting trial practicum, analyzing worksheets and reconstructing new worksheet. The results showed (1) only the practical aspect fulfilled to the criteria of quite valid, while the others were still less valid. (2) In general, the achievement scores of Worksheets in KTSP 2006 were higher than those of Worksheet in K-13, due to lower Basic Competencies demands. Furthermore, new Worksheet was constructed which is expected to be able to be qualified to the 4 concepts tested.